The Decision-making Path of the Intellectual Capital’s Employment under the Impact of Family Network Will：An Empirical Study - Cai, Li (Advances in Social Sciences Research Journal, 2014)
Based on the correlation between the intellectual capital theory and the planned behavior theory in the field of behavioral science, this study established a path model that reflects the impact of the Family Network Will (FNW) on the intellectual capital’s employment. The reliability and reasonability of the model were calculated and tested using structural equations. The results of the study indicated that the comprehensive indicator of the FNW on the perceived subjective behavior and experience, behavioral control and norm, and attitude, had a significant impact on the model. Attitude is the primary dependent factor in behavioral decision-making. As the attitude varies, the decision-making path varies accordingly. With the weakening of the FNW, the family’s direct or indirect control will gradually change to the natural development mode. The FNW-based employment has negative impact on fair competition, and on employers and the individual’s accumulation of high-quality human capital.